2023
DOI: 10.1097/aog.0000000000005199
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Adverse Childhood and Adult Experiences During Prenatal Care

Abstract: Screening for adverse childhood and adult experiences in prenatal care allows clinicians to address past and present adversity and trauma, with a goal of improving perinatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 122 publications
0
3
0
Order By: Relevance
“…An appropriate time to screen may be during a visit when trust has already been established and the initial reason for entry to care has been addressed. 62 Midwives and other advanced providers are wellpositioned to assess for ACEs, as they are often the first to see patients in provider offices, hospitals, and rural areas and may be the primary care providers. 63 Furthermore, women with a history of ACEs were found to have more anxiety, depression, and posttraumatic stress as well as increased substance use, including tobacco and alcohol, during the perinatal period.…”
Section: Implications For Practicementioning
confidence: 99%
See 2 more Smart Citations
“…An appropriate time to screen may be during a visit when trust has already been established and the initial reason for entry to care has been addressed. 62 Midwives and other advanced providers are wellpositioned to assess for ACEs, as they are often the first to see patients in provider offices, hospitals, and rural areas and may be the primary care providers. 63 Furthermore, women with a history of ACEs were found to have more anxiety, depression, and posttraumatic stress as well as increased substance use, including tobacco and alcohol, during the perinatal period.…”
Section: Implications For Practicementioning
confidence: 99%
“…Screening should also inquire about strengths and resilience which can be incorporated into the patient's care plan to maintain their emotional safety. 62 Mishra et al 64 reported that patients have a positive attitude to ACE screening if health care providers showed empathy and caring behaviors and provided appropriate care and referral resources to address their needs after an ACE evaluation. Collaborating and coordinating the patient's care across settings and specialties, using a whole-person approach, increases opportunities for successful TIC.…”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation